EFFORTS TO IMPROVE LEARNING OUTCOMES OF DROPSHOT TECHNIQUES BY MODIFYING HIT TARGETS IN BADMINTON GAMES - Martono (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2025)
Students learning outcomes in badminton game material are still lacking due to students at SMP Negeri 2 Liang who have difficulty learning the basic dropshot technique in badminton. So there is a need for modified learning activities to make it aesier for students to learn the material being taught and can improve learning outcomes. Therefore, this classroom action research aims to determine the increase in student learning outcomes in the dropshot hitting material in the game of badminton by modifying learning for students at SMP Negeri 2 Liang. The time for conducting the research was from February to March 2024. The subjects of this research were 28 class VIII students. The research data was obtained through a dropshot punch proficiency test through an initial test and a final test after students took part in modified learning activities. Data analysis uses the percentage of learning completeness. Based on the results of data analysis, it was found that the average student learning outcomes in the psychomotor domain of cycle I was 31.25 and cycle II was 37.12, the affective domain of cycle I was 15.10 and cycle II was 15.12, and the cognitive domain of cycle I was 19.26 and cycle II was 21.80. It was concluded that there was an increase in student learning outcomes by modifying the target of badminton dropshot shots for students at SMP Negeri 2 Liang